Accident Music - R. Gibson (Law Text Culture, 2009)
[Images] + [text] - Set up the scene. It’s this kind of town. Sunrise hustles fresh air in from the ocean. A day spent near the harbour gives the full history of radiance. At night you can hear accident music in fog horns and pilot bells....